Association between air pollution and rhinitis incidence in two European cohorts. (June 2018) - Burte, Emilie; Leynaert, Bénédicte; Bono, Roberto; Brunekreef, Bert; Bousquet, Jean; Carsin, Anne-Elie; De Hoogh, Kees; Forsberg, Bertil; Gormand, Frédéric; Heinrich, Joachim; Just, Jocelyne; Marcon, Alessandro; et al.
Abstract: Background: The association between air pollution and rhinitis is not well established. Aim: The aim of this longitudinal analysis was to study the association between modeled air pollution at the subjects' home addresses and self-reported incidence of rhinitis. Methods: We used data from 1533 adults from two multicentre cohorts' studies (EGEA and ECRHS). Rhinitis incidence was defined as reporting rhinitis at the second follow-up (2011 to 2013) but not at the first follow-up (2000 to 2007). Annual exposure to NO2, PM10 and PM2.5 at the participants' home addresses was estimated using land-use regression models developed by the ESCAPE project for the 2009–2010 period. Incidence rate ratios (IRR) were computed using Poisson regression. Pooled analysis, analyses by city and meta-regression testing for heterogeneity were carried out. Results: No association between long-term air pollution exposure and incidence of rhinitis was found (adjusted IRR (aIRR) for an increase of 10 μg·m −3 of NO2: 1.00 [0.91–1.09], for an increase of 5 μg·m −3 of PM2.5 : 0.88 [0.73–1.04]). Similar results were found in the two-pollutant model (aIRR for an increase of 10 μg·m −3 of NO2: 1.01 [0.87–1.17], for an increase of 5 μg·m −3 of PM2.5 : 0.87 [0.68–1.08]). Results differed depending on the city, but no regional pattern emerged for any of the pollutants. Conclusions: This study did not find any consistent evidence of an association between long-term air pollution and incident rhinitis. Highlights: Rhinitis is an important and prevalent public health issue. No studies have assessed the effect of outdoor air pollution on rhinitis incidence in adults. Long-term exposure to NO2, PM10 and PM2.5 was not associated with incident rhinitis. Our results differed across cities.